Fundamentals of Nuclear Safety State Management in Ukraine - PETROVSKA, Iryna I.; ROZVADOVSKY, Volodymyr I.; PTASHNYK, Iryna R.; GRYTSAN, Olga A. (Journal of Advanced Research in Law and Economics, 2018)
The object of the research is the relationships ensuring nuclear safety in Ukraine. The methodological basis of this study is modern general scientific methods and techniques of cognition, scientific theories about the state and law, the organization of public administration, development in the field of philosophy of law, public administration, administrative law and process, sociology. The work uses dialectical, structural-functional, historical, comparative-legal, system-structural and other methods. The purpose of this research is to characterize the measures provided by the national legislation of Ukraine for ensuring nuclear safety, which are carried out by authorized state bodies and officials. To achieve this purpose, the following tasks are set: to define the content of the concepts of ‘national security’ and ‘nuclear safety’, elements of the mechanism of management in the nuclear sphere; to allocate legal bases for ensuring nuclear safety and authorized entities; to carry out an analysis of the control system for nuclear safety in Ukraine; to characterize the research activity and international cooperation of Ukraine in the nuclear sphere; to characterize administrative services in the nuclear sphere; to investigate the activities of the governing body on the management of nuclear power plants in Ukraine – the State Enterprise National Nuclear Energy Generating Company ‘Energoatom’